Correlation between religion, spirituality and perception of healthcare services utilisation in Poland during COVID-19 pandemic - Tuczyńska, Magdalena; Matthews-Kozanecka, Maja; Baum, Ewa (PeerJ, 2022)
Background The worldwide transmission of SARS CoV-2 caused the COVID-19 pandemic and had an impact on healthcare provision. The disruption of reliance on the health system during the COVID-19 pandemic posed a clear threat to public trust. Religiosity, like spirituality, is believed to have a positive influence on people’s lives, enabling them to cope with illness, stress, and sudden life changes. In practice, although the terms religiosity and spirituality have similar meanings and are related, they are not identical concepts. The aim of this study is to compare the perceptions of the accessibility and quality of healthcare services provided before and during the COVID-19 pandemic in Poland by religious/spiritual people compared to those for whom religion and spirituality have little or no importance in their lives. Methodology This cross-sectional study was based on the authors’ questionnaire, carried out during the third wave of the COVID-19 pandemic in Poland. Participants in the study were people living in various regions of Poland over 18 who were willing to complete the questionnaire voluntarily. The number of people sampled was two hundred and sixty-four. Convenience sampling method was used for this study. Statistical calculations were performed using Statistica 13 software from TIBCO and PQStat from PQStat Software and were based on the Kruskal-Wallis test, multiple regression model, the chi2 test of independence or the Mann-Whitney test. The result was considered statistically significant when p < α. The significance level was taken as α = 0.05. Results Two hundred and sixty-three respondents answered the questionnaire. Among them, 181 (69%) were women, and 82 (31%) were men. It was shown that religion is more important for women than for men and women who report a high role of religion in their lives rated the quality of healthcare services better before and during the COVID-19 pandemic. It was also concluded that religious people for whom religion played a major role and those who were helped by spiritual life rated accessibility and quality higher both before and during the pandemic. Conclusions Religious/spiritual people, through their more positive attitudes towards the world, were thought to rate access and quality of healthcare services better. Regardless of religious affiliation, the help of spiritual life during the pandemic or the importance of religion in life in all respondents, perception of healthcare services utilisation were decreased by the pandemic. This prompts thoughts on the implementation of spiritual assistance as a supportive measure to mitigate the effects of the pandemic.
Keywords: COVID-19; Religion; Spirituality; Healthcare; Utilisation; Accessibility; Quality